Heritability of Problem Drinking and the Genetic Overlap with Personality in a General Population Sample - De Moor, Marleen H.; Vink, Jacqueline M.; van Beek, Jenny H.; Geels, Lot M.; Bartels, Meike; de Geus, Eco J.; Willemsen, Gonneke; Boomsma, Dorret I. (Frontiers in Genetics, 2011)
This study examined the heritability of problem drinking and investigated the phenotypic and genetic relationships between problem drinking and personality. It was conducted in a sample of 5,870 twins and siblings and 4,420 additional family members from the Netherlands Twin Register. Data on problem drinking (assessed with the AUDIT and CAGE; 12 items) and personality (NEO-FFI; 60 items) were collected in 2009/2010 through surveys. Factor analysis on the AUDIT and CAGE items showed that the items clustered on two separate but highly correlated (r=0.74) underlying factors. A higher order factor was extracted that reflected those aspects of problem drinking that are common to the AUDIT and CAGE , which showed a heritability of 40%. The correlations between problem drinking and the five dimensions of personality were small but significant, ranging from 0.06 for Extraversion to -0.12 for Conscientiousness. All personality dimensions (with broad-sense heritabilities between 32% and 55%, and some evidence for non-additive genetic influences) were genetically correlated with problem drinking. The genetic correlations were small to modest (between |0.12-0.41|). Future studies with longitudinal data and DNA polymorphisms are needed to determine the biological mechanisms that underlie the genetic link between problem drinking and personality.